Anti-VEGF agents for the treatment of diabetic macular edema - S.G. Sergushev; E.N. Khomyakova (РМЖ "Клиническая офтальмология")
S.G. Sergushev1, E.N. Khomyakova2 1A.I. Burnazyan Federal Medical Biological Center of the Federal Medical Biological Agency of Russia, Moscow, Russian Federation 2M.F. Vladimirskiy Moscow Regional Research and Clinical Institute, Moscow,   Russian Federation According to the International Diabetes Federation, in 2017, approximately 425 million adults were living with diabetes. Diabetic retinopathy and diabetic macular edema (DME) are the leading causes of vision loss in the working-age population. They result in a significant burden on patients and society. Until recently, laser retinal photocoagulation was recognized as the only treatment for DME. However, the current preferred first-line therapy for DME are anti-VEGF agents. This article highlights the results of major studies demonstrating the advantages of anti-VEGF therapy over laser retinal photocoagulation in terms of vision improvement, i.e., VIVID/VISTA and Protocol I. In addition, current anti-VEGF agents for DME and their characteristics potentially affecting the efficacy (i.e., the number of angiogenic targets, affinity, the duration of VEGF suppression) are reviewed. The results of comparative independent study Protocol T and two meta-analyses to determine the best-choice medication for DME are addressed. This paper also describes in detail post-hoc analyses of VIVID/VISTA studies on the efficacy of aflibercept in patients with or without subretinal fluid at baseline, patients with uncontrollable diabetes, and previously treated patients. Studies on aflibercept in routine clinical practice are discussed to illustrate the possibility to achieve the results of randomized trials in daily practice with adequate patien t management and regular treatment. Keywords: diabetes, diabetic retinopathy, macular edema, laser retinal photocoagulation, VEGF, anti-VEGF agents, aflibercept, Eylea. For citation: Sergushev S.G., Khomyakova E.N. Anti-VEGF agents for the treatment of diabetic macular edema. Russian Journal of Clinical Ophthalmology. 2019;19(4):238–244.